2008
DOI: 10.7863/jum.2008.27.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver and Interobserver Reproducibility of 3-Dimensional Power Doppler Vascular Indices in Assessment of Solid and Cystic-Solid Adnexal Masses

Abstract: Objective. The purpose of this study was to assess the intraobserver and interobserver reproducibility of 3-dimensional (3D) power Doppler angiography-derived vascular indices in evaluation of vascularized solid and cystic-solid adnexal masses. Methods. Stored 3D power Doppler angiographic volume data from 12 consecutive women with a diagnosis of a complex adnexal mass (6 cystic-solid and 6 solid) evaluated and treated at our institution were retrieved from our database for analysis. Two examiners performed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This group demonstrated that this approach is reproducible. 98 Testa et al reported similar findings using different software in a series of 24 women with solid ovarian masses. 99 Geomini et al reported data from a series of 181 women with adnexal masses.…”
Section: Three-dimensional Ultrasound In Adnexal Pathologysupporting
confidence: 63%
“…This group demonstrated that this approach is reproducible. 98 Testa et al reported similar findings using different software in a series of 24 women with solid ovarian masses. 99 Geomini et al reported data from a series of 181 women with adnexal masses.…”
Section: Three-dimensional Ultrasound In Adnexal Pathologysupporting
confidence: 63%
“…67 Several studies have shown that, whatever the approach used, manual or spherical sampling, reproducibility is high between observers. [69][70][71] Regarding to the contribution to diagnosis of ovarian cancer, Geomini et al reported a multicenter prospective study concluding that the use of 3D ultrasound significantly improves the prediction of malignancy as compared to 2D ultrasonography. 72 Alcazar et al 73 information to gray-scale imaging than that provided by subjective quantification by 2D PD.…”
Section: Adnexal Tumorsmentioning
confidence: 97%
“…Intraobserver and interobserver reproducibility were high for all 3DPD vascular indices, and 3DPD ultrasound was a reproducible technique for the offline assessment of stored 3D volume data on vascularized adnexal masses. 73 Alcázar and Prka 74 reported that difficulties encountered on performing different vascular sampling methods do not seem to significantly affect the reproducibility of 3DPD index calculations. Moreover, Kudla and Alcázar 75 concluded that the sphere sample size does not affect the reproducibility of measurements of 3DPD vascular indices in adnexal masses.…”
Section: Quantitative 3dpd Histogram Analysismentioning
confidence: 99%